Social and Cultural Integration: A Discourse Analysis of Islamic Themes in the Basis Magazine, 1998–2000 - Yuliantri, Rhoma Dwi Aria (Diponegoro University, 2024)
This article examines the discourse on Islam found in articles published in Basis from 1998 to 2000. Basis is a cultural magazine founded in Yogyakarta by members of the Society of Jesus (SJ) in 1951. Since 1998, Basis has regularly featured writings on Islamic themes contributed by both Muslim and non-Muslim intellectuals. This research aims to understand why Basis, with its Catholic missionary vision and spirit, embraced Islamic themes during the 1998–2000 period and to what extent these Islamic and Islamic-themed articles reflect the journal's mission of interreligious dialogue in response to the